A theory of urban squatting and land-tenure formalization in developing countries - Jan Keith Brueckner; Harris Selod (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper offers a new theoretical approach to urban squatting, reflecting the view that squatters and formal residents compete for land within a city. The key implication of this view is that squatters squeeze the formal market, raising the price paid by formal residents. The squatter organizer, however, ensures that this squeezing is not too severe, since otherwise the formal price will rise to a level that invites eviction by landowners (defensive expenditures by squatter households also help to forestall eviction). Because eviction is thus absent in equilibrium, the model differs crucially from previous analytical frameworks, where eviction occurs with some probability.
Keywords: R00; R31; O18; 330; Tenure Choice; Slum; Städtische Wohnungsversorgung; Theorie; Entwicklungsländer